UTAR second hand E-Commerce application - Chua, Calvin Kai Pin (2024)
As internet technologies grow rapidly, some offline retail stores and vendors started to move their business to E-commerce. This trend has been keeping growing until now as people having their own mobile phone is ubiquitous. More and more E-commerce platforms have been introduced and are being used by offline retail stores and vendors as their first step toward E-commerce. There is a variety of useful features are introduced in the E-commerce platform to improve business processes. There are three similar E-commerce platforms have been reviewed. However, there are some limitations in the E-commerce platforms which need to be improved. Hence, the objective of the project is to develop a second-hand E-commerce application. Also, to identify the basic and main components and processes in e-commerce. After that, complete the 6 modules which include the buyer module, seller module, location distance module, community module, item module, and authentication module. Lastly, integrating these 6 modules becomes an application.